Penerapan Humanitarian Intervention dalam Hukum Internasional sebagai Upaya untuk Mencegah Pelanggaran HAM. Studi Kasus: Konflik di Kosovo, Libya dan Suriah - Hermanto, Hanisyah Claudya; Mevalia, Kaila Aura; Widiastutie, Sophiana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Humanitarian Intervention is a phenomenon that emerged in the modern era as a result of extreme historical experiences that have caused a horrifying number of casualties. Humanitarian Intervention represents the application of international law aimed at protecting civilians from excessive violations of human rights. Several instances of this phenomenon are reflected in three major conflicts: Kosovo, Libya, and Syria. Using qualitative research methods and literature review as data sources, this article seeks to highlight a comparison of these three cases regarding the effectiveness of Humanitarian Intervention implementation. It was found that in the cases of Kosovo and Libya, both demonstrated significant and organized international support through NATO. Conversely, Humanitarian Intervention failed to be effectively implemented in Syria due to geopolitical factors and the lack of international consensus.